2015
DOI: 10.1038/cddis.2015.150
|View full text |Cite
|
Sign up to set email alerts
|

LincHOTAIR epigenetically silences miR34a by binding to PRC2 to promote the epithelial-to-mesenchymal transition in human gastric cancer

Abstract: lncRNAs play important roles in the epigenetic regulation of carcinogenesis and progression. Previous studies suggest that HOTAIR contributes to gastric cancer (GC) development, and the overexpression of HOTAIR predicts a poor prognosis. In this study, we found that HOTAIR was more highly expressed in diffuse-type GC than in intestinal type (P=0.048). In the diffuse type, there is significant relationship between HOTAIR expression and DFS (P<0.001). CDH1 was downregulated in diffuse-type GC tissues (P=0.0007) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
143
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 47 publications
4
143
0
2
Order By: Relevance
“…It has been confirmed that lncRNAs regulate tumor progression through modulating gene expression at the epigenetic, transcriptional and posttranscriptional levels, in which interaction with miRNAs is important. For instance, HOTAIR epigenetically silences miR-34a, leading to enhanced EMT in human gastric cancer [25], and MIR31HG exhibits oncogenic properties by sponging miR-193bin pancreatic ductal adenocarcinoma [26]. Our results showed that HOXA-AS2 negatively regulated miR-373 expression by sponging it.…”
Section: Discussionmentioning
confidence: 50%
“…It has been confirmed that lncRNAs regulate tumor progression through modulating gene expression at the epigenetic, transcriptional and posttranscriptional levels, in which interaction with miRNAs is important. For instance, HOTAIR epigenetically silences miR-34a, leading to enhanced EMT in human gastric cancer [25], and MIR31HG exhibits oncogenic properties by sponging miR-193bin pancreatic ductal adenocarcinoma [26]. Our results showed that HOXA-AS2 negatively regulated miR-373 expression by sponging it.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, Wu et al demonstrated that HOTAIR contributes to the direct suppression of E-cadherin by recruiting enhancer of zeste homolog 2 (EZH2) to the E-cadherin promoter [42]. Supporting evidence were found that HOTAIR expression levels were negatively correlated with those of E-cadherin in gastric cancer and oral squamous cell carcinoma tissues [41,42]. Besides, Hong et al demonstrated that HOTAIR also functions as a ceRNA for miR-217, thus regulating HIF-1α/AXL signaling and promoting EMT process in renal cell carcinoma [43].…”
Section: Introductionmentioning
confidence: 58%
“…Further study revealed that HOTAIR-PRC2 complex epigenetically silences a tumor-suppressive microRNA miR-34a, which controls the downstream targets c-Met (HGF/c-Met/Snail pathway) and Snail, thus contributing to the process of EMT and tumor metastasis in gastric cancer (Fig. 2b, i) [41]. Moreover, Wu et al demonstrated that HOTAIR contributes to the direct suppression of E-cadherin by recruiting enhancer of zeste homolog 2 (EZH2) to the E-cadherin promoter [42].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that lncRNAs are required for epigenetic regulation of target genes through binding with PRC2, thus contributing to cancer progression [30, 35, 36]. EZH2 and SUZ12, as two core components of PRC2 complex, have been shown to be involved in cancer progression [37-39].…”
Section: Resultsmentioning
confidence: 99%